The Antimicrobial and Immunomodulatory Function of RNase 7 in Skin - Rademacher, Franziska; Dreyer, Sylvia; Kopfnagel, Verena; Gläser, Regine; Werfel, Thomas; Harder, Jürgen (Frontiers in Immunology, 2019)
The human ribonuclease RNase 7 has been originally isolated from human skin and is a member of the human RNase A superfamily. RNase 7 is constantly released by keratinocytes and accumulates on the skin surface. The expression of RNase 7 in keratinocytes can be induced by diverse stimuli such as cytokines, growth factors and microbial factors. RNase 7 exhibits a potent broad spectrum of antimicrobial activity against various microorganisms and contributes to control bacterial growth on the skin surface. The ribonuclease and antimicrobial activity of RNase 7 can be blocked by the endogenous ribonuclease inhibitor. There is also increasing evidence that RNase 7 exerts immunomodulatory activities and may participate in antiviral defense. In this review we discuss how these characteristics of RNase 7 contribute to innate cutaneous defense and highlight its role in skin infection and inflammation. We also speculate how a potential dysregulation of RNase 7 promotes inflammatory skin diseases and if RNase 7 may have therapeutic potential.